Types of Modality in News Item is Used in the Texts News in the Jakarta Post Newspaper - T. Aldilla Syahira; T. Silvana Sinar; Masdiana Lubis (Budapest International Research and Critics University, 2021)
This research aimed to find out types of modality and to explain how the most dominant types of modality in news item is used in the texts news in The Jakarta Post newspaper. This research was conducted by using corpus analysis as the appropriate tool to analyze the online written text. The data were taken from the source of Jakarta Post newspaper which published online from the 1st August until 31th December 2019. The sources varied in four themes i.e. politic, education, sports and economic news. As a result, the researcher found 2 types of modality there are modalization and modulation. These types have 2 types of intermediacy on each, probability and usuality for modalization and obligation and inclination for modulation.